088 Brainstem progressive multifocal leukoencephalopathy. Issue 6 (27th May 2022) - Hawken, Jonathan; Pearson, Owen; Smith, Rachel; Sadiq, Shaheena; Ingram, Gillian
Abstract : Progressive multifocal leukoencephalopathy (PML) is a rare but potentially fatal viral brain infection seen in immunocompromised patients and in patients with multiple sclerosis (MS) on disease-modifying treatments such as natalizumab. The most frequent reported pattern of PML is that of large subcortical T2 and diffusion hyperintense lesions. Brainstem PML, although previously reported, is rare and therefore easily missed. A 46-year-old lady with a diagnosis of MS on treatment with natalizumab for 5 years, serum JC virus high positive; presented with worsening of long-standing unsteadiness. Prior imaging showed multiple supra and infra-tentorial T2 hyperintensities; however, repeat imaging at presentation demonstrated an increase in size and number of lesions in the medulla, more confluent lesions in the pons with restricted diffusion, but no change in the supra-tentorial lesion load. Natalizumab therapy was suspended and a lumbar puncture revealed a high JC virus titre (1, 090, 000 m/L), confirming a diagnosis of PML. Serial MRI's showed lesion progression with contrast enhancement at 10–12 weeks with associated CSF pleocytosis indicating immune reconstitution inflammatory syndrome. The patient was managed conservatively and her disability remained stable. PML affecting the brainstem is under-reported in the literature. Awareness and prompt recognition of the condition is needed to minimise complications. Jonathan: hawken@wales.nhs.uk 69